2015
DOI: 10.1159/000437054
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Nonalcoholic Fatty Liver Disease in Young Adults Born Preterm

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is considered the hepatic manifestation of metabolic syndrome. Accelerated catch-up in weight during infancy in subjects born at full term has been associated with increased risk for NAFLD in adulthood, but this association has not been studied in subjects born preterm. Methods: In 162 young adults born at a gestational age <36 weeks, we assessed the associations between fatty liver index (FLI, 0-100) and birth weight standard deviation score and first-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The results of other famine studies were consistent with ours . There is also compelling evidence indicating that people who were stunted during infancy and childhood or who had low birth weight but subsequently had a continuous high‐fat diet (HFD) had higher susceptibility to fatty liver in later life . We call this a feast after famine model, which may reflect the high prevalence of NAFLD in China under their special nutrition history.…”
Section: Introductionsupporting
confidence: 87%
“…The results of other famine studies were consistent with ours . There is also compelling evidence indicating that people who were stunted during infancy and childhood or who had low birth weight but subsequently had a continuous high‐fat diet (HFD) had higher susceptibility to fatty liver in later life . We call this a feast after famine model, which may reflect the high prevalence of NAFLD in China under their special nutrition history.…”
Section: Introductionsupporting
confidence: 87%
“…Another study found that accelerated weight gain in infancy was associated with FLI but LBW and gestational age were not, but this study was limited to a young adults born preterm. 13 Support for the hypotheses that both low birthweight and high birthweight are associated with liver fat can be found in the animal literature. Higher-fat diets have been associated with both increased and decreased weight and corresponding adverse effects on the liver.…”
Section: Discussionmentioning
confidence: 77%
“…Late PTB was associated with higher ALT, AST and FLI (though not GGT) values in another study; 12 the majority of the PTB in our study were late, but the mean differences in both of our cohorts are much smaller than found in this previous study. Another study found that accelerated weight gain in infancy was associated with FLI but LBW and gestational age were not, but this study was limited to a young adults born preterm 13 …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations